Clinical evaluation of the lot-to-lot consistency of an enterovirus 71 vaccine in a commercial-scale phase IV clinical trial. Issue 5 (30th November 2022) - Chen, Jinhua; Jin, Pengfei; Chen, Xiaoqi; Mao, Qunying; Meng, Fanyue; Li, Xinguo; Chen, Wei; Du, Meizhi; Gao, Fan; Liu, Pei; Li, Xiujuan; Guo, Changfu; et al.
ABSTRACT: Objective: To evaluate the immunogenicity, safety and lot-to-lot consistency of an inactivated enterovirus 71 (EV71) vaccine cultured in bioreactors with different specifications after full immunization. Methods: A randomized, double-blind trial was performed in 3, 000 children aged 6 35 months with six vaccine batches, which were prepared in 40 L and 150 L bioreactors for three consecutive batches respectively. Children were immunized on day 0 and 28, serum samples were collected on day 0 and 56, and neutralizing antibody titers were determined by the microcytopathic method. Immediate reactions were recorded within 30 min, local and systemic symptoms were recorded within 0 28 days, and serious adverse events were recorded within 6 months. Results: After immunization with two doses of the inactivated EV71 vaccine, the neutralizing antibody GMT was 825.52 ± 4.09, and the positive conversion rate was 96.18%, with no significant difference. The 95% CI of the serum neutralizing antibody GMT ratio between the two groups after immunization with the three vaccine batches produced in the 150 L and 40 L bioreactors ranged from .67 1.5. The overall incidence of adverse reactions, mainly grade 1 reactions, for all 6 batches from 0 to 28 days after vaccination was 49.62%, with no significant difference (p = .8736). The incidence of systemic adverse reactions, primarily fever and diarrhea, was 45.14%; the incidence of local adverse reactions, primarily erythema and tenderness, was 9.43%. Conclusion: The EV71 vaccine was highly immunogenic and safe in children aged 6–35 months, and 6 consecutive batches produced by the two bioreactors with different specifications were consistent.